Electronic Properties of {112} and {110} Twin Boundaries in Anatase TiO2. Issue 12 (9th October 2019) - Quirk, James A.; Lazarov, Vlado K.; McKenna, Keith P.
Abstract: First‐principles calculations of the electronic structure and charge‐trapping behavior of Σ3 {112} and Σ1 {110} twin boundaries (TBs) in anatase TiO2 are performed using an accurate hybrid density functional theory approach. The former is characterized experimentally using transmission electron microscopy (TEM) and very good agreement on the structure is found. The {110} twin has not yet been observed but TEM and scanning tuneling microscopy (STM) image simulations are presented to aid experimental identification. Holes are found to trap in a polaronic configuration at both the twin boundaries. The {112} TB presents more favorable sites for hole polaron formation at the boundary with trapping energies 0.16–0.18eV, more favorable than the bulk. The {110} TB presents hole polaron trapping sites ranging from 0.07 eV, less favorable, to 0.14 eV, more favorable, than the bulk. Neither boundary is found to favor electron trapping, indicating they are relatively benign to the performance of anatase as an n ‐type conductor. Abstract : Two twin boundaries (TB) in anatase are investigated using an accurate hybrid density functional theory approach. Both TBs are found to provide sites for deep hole trapping but no sites for electron trapping. These TBs are expected to be relatively benign with respect to electron mobility in anatase.